Compound Shenma Jingfu granule alleviates cerebral ischemia via HIF-1α-mediated promotion of angiogenesis - Ruihua He; Yi Xu; Jingxue Liu; Jing Liu; Jing Chen; Xufang Wang; Lei Qiu; Jin Huang (BMC, 2024)
Abstract Background Shenma Jingfu Granule, a traditional Chinese medicine formula, has been used clinically for the treatment of cerebral circulation insufficiency. However, the mechanism involved in alleviating cerebral ischemia has not yet been fully elucidated. Methods An integrated approach involving network pharmacology and transcriptomics was utilized to clarify the potential mechanisms of SMJF Granule. Molecular docking and surface plasmon resonance (SPR) were employed to identify potential targets and ingredients of SMJF Granule. The anti-CI effect of SMJF Granule was determined on the middle cerebral artery occlusion (MCAO) model by using hematoxylin-eosin (H&E) and Nisslʼs staining, as well as triphenyl tetrazolium chloride (TTC) staining, and the potential targets involved in the mechanisms were validated by RT-qPCR and western blotting. Results Integrated analysis revealed the mechanism of SMJF Granule intervening in CI injury might be related to the HIF-1 signaling pathway and angiogenesis. Molecular docking and SPR assays demonstrated robust binding interactions between key compounds like salvianolic acid A and naringenin with the core target HIF-1α protein. The experiment confirmed that SMJF Granule lowered neurological scores, diminished infarct volume, and alleviated histopathological changes in vivo. The possible mechanism of SMJF Granule was due to regulating HIF-1 pathway, which contributed to up-regulating expression of VEGF and vWF in the penumbral region, showing a significant promotion of angiogenesis. Conclusion SMJF Granule promoted angiogenesis through HIF-1α pathway, thereby alleviating cerebral ischemia injury. In addition, our findings provide some evidence that SMJF Granule is a candidate compound for further investigation in treating CI in the clinical. Graphical Abstract